The Effect of Length of Work on Dry Eyes Disease in Madurese Becak Workers, Sumenep Regency - Bragastio Sidharta; RA. Erlinda Manggarsari; Hanna Cakrawati (Universitas Muhammadiyah Malang, 2023)
Dry eye disease (DED) is a disorder of the tear film caused by reduced tear production giving complaints that the eyes feel dry, and gritty and cause a burning sensation, which is one of the reasons patients come to see a doctor. The causes of DED are very multifactorial where ocular, anatomical, systemic, and environmental factors have been reported by several studies which state that there is a relationship between environmental factors such as pollutants from motorized vehicles having a role in the incidence of increased DED. Sumenep Regency was once a city of a thousand pedicabs and until now they are still the favorite choice for the people there. This research is an analytic observational with a cross-sectional approach. Data on the characteristics of the study subjects, length of work, and degree of DED complaints were collected and DED complaints were assessed using the Ocular Surface Disease Index (OSDI) questionnaire. The data were processed and analyzed using the Spearman correlation test to determine the effect of length of service on the level of DED complaints. A moderate strength (Spearman correlation = 0.441) relationship exists between the length of work and the degree of DED complaints in pedicab drivers.